Carboxyl functionalised MWCNT/polymethyl methacrylate bone cement for orthopaedic applications. (August 2014) - Ormsby, Ross W; Modreanu, Mircea; Mitchell, Christina A; Dunne, Nicholas J
The incorporation of carboxyl functionalised multi-walled carbon nanotube (MWCNT-COOH) into a leading proprietary grade orthopaedic bone cement (Simplex P™) at 0.1 wt% has been investigated. Resultant static and fatigue mechanical properties, in addition to thermal and polymerisation properties, have been determined. Significant improvements ( p  ≤ 0.001) in bending strength (42%), bending modulus (55%) and fracture toughness (22%) were demonstrated. Fatigue properties were improved ( p  ≤ 0.001), with mean number of cycles to failure and fatigue performance index being increased by 64% and 52%, respectively. Thermal necrosis index values at ≥44℃ and ≥55℃ were significantly reduced ( p  ≤ 0.001) (28% and 27%) versus the control. Furthermore, the onset of polymerisation increased by 58% ( p  < 0.001), as did the duration of the polymerisation reaction (52%). Peak energy during polymerisation increased by 672% ( p  < 0.001). Peak area of polymerisation increased by 116% ( p  < 0.001) indicating that the incorporation of MWCNT-COOH reduced the rate of polymerisation significantly. A non-significant reduction (8%) in percentage monomer conversion was also recorded. Raman spectroscopy clearly showed that the addition of MWCNT-COOH increased the ratio between normalised intensities of the G-Band and D-Band ( IG /ID ), and also increased the theoretical compressive strain (−1.72%) exerted on the MWCNT-COOH by the Simplex P™ cement matrix. Therefore, demonstrating a level of chemical interactivity between the MWCNT-COOH and the Simplex P™ bone cement exists and consequently a more effective mechanism for successful transfer of mechanical load. The extent of homogenous dispersion of the MWCNT-COOH throughout the bone cement was determined using Raman mapping.